1993
DOI: 10.1093/oxfordjournals.humrep.a137874
|View full text |Cite
|
Sign up to set email alerts
|

Sequential clomiphene citrate and human menopausal gonadotrophin for ovulation induction: comparison to clomiphene citrate alone and human menopausal gonadotrophin alone

Abstract: The need for frequent injections and monitoring, the possibility of multiple gestations, and the higher cost compared to clomiphene citrate, prevents many clinicians from using human menopausal gonadotrophin (HMG) for ovulation induction. A sequential medication regimen, in which HMG is taken after clomiphene, overcomes these problems. We retrospectively compared per cycle fecundity and birth rates in 119 cycles of clomiphene-HMG, 524 cycles of clomiphene alone, 57 cycles of HMG alone, and 79 cycles of concurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
28
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 0 publications
8
28
1
Order By: Relevance
“…It has been shown in many studies in the literature that the use of FSH and hMG is superior to CC use (24)(25)(26)(27). Although we observed that gestational rates were low in the CC group, we could not show the difference due to the small sample size.…”
Section: Discussioncontrasting
confidence: 87%
“…It has been shown in many studies in the literature that the use of FSH and hMG is superior to CC use (24)(25)(26)(27). Although we observed that gestational rates were low in the CC group, we could not show the difference due to the small sample size.…”
Section: Discussioncontrasting
confidence: 87%
“…This is in agreement with other studies which show nearly doubling of estradiol levels per follicle in CC+HMG group compared with CC alone. 18 Good ovulation and pregnancy rates were achieved with CC with IUI in the current study. The overall ovulation rate was 91.3%.…”
Section: Discussionsupporting
confidence: 56%
“…Apparently, clomiphene regimen used in the current study does not have pronounced anti-estrogenic effects on the endometrium. A study carried out by Dickey et al 18 concluded that increased fecundity when HMG is administered after clomiphene compared to clomiphene alone is related to doubling of implantation rate per follicle. The estradiol level per follicle also nearly doubled for clomiphene-HMG compared to clomiphene alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our series we observed that 25.5% of our patients were overweight and 19.2% were obese. Authors like DICKEY [8] think that weight correction is essential and can alone restore ovulation.…”
Section: Epidemio-clinical Characteristicsmentioning
confidence: 99%